First Report of Brown Ring Patch Caused by Waitea circinata var. circinata on Poa annua in Pennsylvania - Fidanza, M A (Plant disease, 2009)
In late May and early June of 2008, bright yellow, thin, irregular-shaped rings that were 10 to 15 cm in diameter were observed on 30% of an annual bluegrass (Poa annua L.) putting green in Coopersburg, PA. The 46-year-old silt-loam soil green was mowed at a 3.1-mm height and consisted of 80% annual bluegrass and 20% creeping bentgrass (Agrostis stolonifera L., unknown cultivar). During the appearance of ring symptoms, the overall minimum and maximum daily air temperature ranged from 19.9 to 31.1°C, respectively, along with 40.3 mm of total rain accumulation. In late May, only individual affected annual bluegrass plants exhibited a bright yellow chlorosis of upper and lower leaf blades and crown. By early June, affected annual bluegrass plants appeared dark brown and water soaked, turning reddish brown and then tan as they dessicated, wilted, and died. Fungal mycelium, similar in appearance to Rhizoctonia spp., was found among affected leaf blades and within the thatch layer. A single fungal isolate was obtained from affected annual bluegrass tissue and grown on potato dextrose agar (PDA) plus 0.1 g of chloramphenicol per liter. Fungal colony morphology and sequencing of the ITS1F/ITS4-amplified rDNA internal transcribed spacer (ITS) region confirmed the isolate as Waitea circinata var. circinata, with ≥90% similar homology match to published W. circinata var. circinata ITS sequences (GenBank Accession No. DQ900586) (2,4). To confirm pathogenicity, the isolate was inoculated onto 6-week-old annual bluegrass (0.001 g of surface-sterilized seed per cm2) grown in 5- × 5-cm2 plastic pots containing autoclaved 70% sand and 30% potting soil. Plants were maintained daily at a 4.0-mm height using a hand-held scissors. One 6-mm-diameter plug of the isolate was removed from the active edge of a 5-day-old culture grown on PDA and placed in contact with the lower leaf blades of the target plants. Four pots were inoculated with the isolate and four pots were inoculated with an isolate-free agar plug for each of two experimental runs. After inoculation, all pots were placed in a moist chamber at 28°C. In both experiments leaf blade chlorosis and a modest amount of aerial mycelium was observed in all four isolate-introduced pots at 5 to 7 days after inoculation. Symptoms were similar to those expressed in the field, and by 21 to 28 days, all isolate-infected plants died, whereas the noninoculated plants remained healthy and nonsymptomatic. W. circinata var. circinata was reisolated from symptomatic tissue of those inoculated plants and again confirmed by colony traits and rDNA ITS region sequences. This pathogen was reported previously as the causal agent of brown ring patch on annual bluegrass and rough bluegrass (Poa trivialis L.) in the western United States. (1,2). To our knowledge, this is the first report of brown ring patch in Pennsylvania. The economic impact of this disease could be significant since intensive fungicide practices are used to produce high-quality putting green surfaces in the region (3). References: (1) C. Chen et al. Plant Dis. 91:1687, 2007. (2) K. de la Cerda et al. Plant Dis. 91:791, 2007. (3) J. Kaminski and F. Wong. Golf Course Mgmt. 75(9):98, 2007. (4) T. Toda et al. Plant Dis. 89:536, 2005